Role of Admission Troponin‐T and Serial Troponin‐T Testing in Predicting Outcomes in Severe Sepsis and Septic Shock - Vallabhajosyula, Saraschandra (J Am Heart Assoc, 2017)
BACKGROUND: Troponin‐T elevation is seen commonly in sepsis and septic shock patients admitted to the intensive care unit. We sought to evaluate the role of admission and serial troponin‐T testing in the prognostication of these patients. METHODS AND RESULTS: This was a retrospective cohort study from 2007 to 2014 on patients admitted to the intensive care units at the Mayo Clinic with severe sepsis and septic shock. Elevated admission troponin‐T and significant delta troponin‐T were defined as ≥0.01 ng/mL and ≥0.03 ng/mL in 3 hours, respectively. The primary outcome was in‐hospital mortality. Secondary outcomes included 1‐year mortality and lengths of stay. During this 8‐year period, 944 patients met the inclusion criteria with 845 (90%) having an admission troponin‐T ≥0.01 ng/mL. Serial troponin‐T values were available in 732 (78%) patients. Elevated admission troponin‐T was associated with older age, higher baseline comorbidity, and severity of illness, whereas significant delta troponin‐T was associated with higher severity of illness. Admission log(10) troponin‐T was associated with unadjusted in‐hospital (odds ratio 1.6; P=0.003) and 1‐year mortality (odds ratio 1.3; P=0.04), but did not correlate with length of stay. Elevated delta troponin‐T and log(10) delta troponin‐T were not significantly associated with any of the primary or secondary outcomes. Admission log(10) troponin‐T remained an independent predictor of in‐hospital mortality (odds ratio 1.4; P=0.04) and 1‐year survival (hazard ratio 1.3; P=0.008). CONCLUSIONS: In patients with sepsis and septic shock, elevated admission troponin‐T was associated with higher short‐ and long‐term mortality. Routine serial troponin‐T testing did not add incremental prognostic value in these patients.